Evoking stress reactivity in virtual reality: a systematic review and meta-analysis. (September 2021) - McCurdy, Bethany H.; van Dammen, Lotte; Finseth, Tor T.; Barnett, Neil P.; Conrady, Roselynn; Leach, Alexis G.; Deick, Andrew F.; Van Steenis, Allissa; Gardner, Reece; Smith, Brandon; Kay, Anita; Shirtcliff, Elizabeth A.
Abstract : Background: Virtual reality (VR) research probes stress environments impossible to create in the real world. To evaluate the magnitude to which VR stress tasks trigger a physiological stress response, we conducted a systematic review and meta-analysis of studies using VR stress tasks that also measure stress biomarkers. Methods: Included papers (n=40) measured cortisol, heart rate (HR), galvanic skin response (GSR), systolic blood pressure (SBP), diastolic blood pressure (DBP), respiratory sinus arrhythmia (RSA), parasympathetic activity (RMSSD), sympathovagal balance (LF/HF), and salivary alpha-amylase (sAA). Effect sizes (ES) and confidence intervals (CI) were calculated based on standardized mean change of baseline and peak biomarker levels. Results: From baseline to post-stressor (ES, CI) analyses showed a statistically significant change in cortisol (0.59, 0.33-0.85), HR (0.67, 0.52-0.80), GSR (0.69, 0.34-1.03), SBP (0.8, 0.36-1.23), DBP (0.65, 0.2-1.09), RSA (-0.59, -0.88 to -0.30), and sAA (0.37, 0.12-0.61). There was no effect for RMSSD and LF/HF. Conclusion: We found that VR stress tasks effectively elicit a varied magnitude of physiological stress reactivity. VR may be an effective tool in stress research.